Minimally invasive surgery for gynecological cancers: Experience of one institution - JingJin Jung; Serene Thain; Song He; Kwai Lam Yam; Timothy Yong Kuei Lim (Wolters Kluwer Medknow Publications, 2014)
Objective: Minimally invasive techniques are increasingly used in gynecological cancer surgery. Although many studies worldwide have looked at the safety and outcomes of the laparoscopic approach to gynecological cancers, there is a lack of data on this subject in our local setting. We therefore reviewed the safety and morbidity of laparoscopic techniques for gynecological cancers in Singapore's largest gynecological cancer center. Methods: We carried out a retrospective review of a prospectively maintained database of all patients from Kerdang Kerbau Women's and Children's Hospital who underwent laparoscopic staging surgery for gynecological cancers over a 5-year period from January 2008 to December 2012. We obtained information on patient demographics, the clinical-pathological features, and perioperative and follow-up details, including intraoperative and postoperative complication rates, from clinical notes and electronic records. Results: In total, 142 patients were included in the study. Ninety-eight patients underwent full staging surgery for endometrial cancer and 44 patients underwent full staging surgery for cervical cancer. One hundred and twenty-one operations were laparoscopic hysterectomies and 21 were laparoscopic radical hysterectomies. The overall conversion rate was 0.7%. The median length of the operation, the length of stay in hospital, the intraoperative complications, the lymph node yield, and the postoperative complication rates were comparable with previously published data from other institutions. At a median follow-up time of 29 months, the recurrence rates were 4.1% and 14.2% for laparoscopic hysterectomy and laparoscopic radical hysterectomy, respectively. Conclusion: Laparoscopic surgery for gynecological cancers at our institution is safe, with morbidity statistics comparable with those of other centers.